Complex training and sprint abilities of young basketball players - Nikolic, D.; Beric, D.; Kocic, M.; Daskalovski, B. (Facta Universitatis: Series Physical Education and Sport, 2017)
The aim of this study was to determine the effects of complex training (a combination of weight training and biomechanically similar plyometric jumps) on the sprint abilities. Young basketball players (N=31, Age=17-18) from OKK "Konstantin" and OKK "Junior" from Nis were divided into two groups: the experimental group (E, n = 16; AVIS = 186,17cm ± 6,50cm; AMAS = 74,75 ± 9,48kg) and control group (K; n = 15; AVIS = 185,15 ± 9,10cm; AMAS = 79,23 ± 11,87kg). The experimental group (E) was made up of the players from basketball team OKK "Konstantin", which in addition to basketball trainings also took part in complex training. The control group (K) was made up of the players from basketball team OKK "Junior", who at that time only took part in basketball trainings. To assess their sprint abilities, three tests were used: the 10x5m Shuttle Test (10x5m), Sprint Fatigue Test (SFT) and Sprint Speed at 15m (S15m). The measurement was done with the help of the photocell "MICROGATE", a parameter which was monitored and the processed time was read in 1/100sec. The experimental program lasted for 12 weeks (2x per week). Data processing was carried out using the SPSS statistical program. To determine the effect of complex training on the sprint abilities of young basketball players, the analysis of covariance ANCOVA was used. The results showed that group E achieved significantly greater progress than group K on the tests: 10x5m and S15m. There was no difference between group E and K on the test SFT. Based on these results we concluded that complex training has positive effects on the development of sprint abilities, as well as on the development of the capacity of changes of direction after a full sprint in young basketball players. However, the aforementioned training method does not lead to improvements in sprint endurance, i.e. it does not lead to an improved index of fatigue.